2019
DOI: 10.1177/2379298119877349
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Mentoring to the Classroom: Lessons for Teachers of Female Undergraduates

Abstract: This article provides pedagogical activities to help develop students into “model mentees.” Being a competent mentee is especially significant for young women who aspire to executive-level management positions. The authors conducted a qualitative study of 14 executive-level women and gained insights into how mentoring relationships affected these women’s careers. For the past four semesters, the findings have been used to enhance the content of two business courses, and they were also used to improve the prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Most of these studies concluded that the academic performance of students had not based on a single factor (Loo, 2017;Lynch & Hennessy, 2017;Mollaeva, 2017;Nogueira, Barros, & Sequeira, 2017;Shoaib, Tariq, Shahzadi, & Ali, 2022). Multiple factors were contributing including classroom environment (Blewitt & Shane, 2019;Shoaib, Anwar, & Rasool, 2022), students' home background (Boateng, Asare, Manu, Sefah, & Adomako, 2020;, study culture (Houtte, 2004;Shoaib, Ali, Anwar, & Abdullah, 2022), the role of teacher Dee, 2006), previous education (Ali et al, 2022;Selvig, Holaday, Purkiss, & Hortsch, 2015), and personal efforts (Arshad, Zaidi, & Mahmood, 2015;Shoaib & Ullah, 2021a). On the other hand, several researchers used different methodological approaches to study students' academic performance in higher education institutions including qualitative, quantitative, mixed methods, observation, content analysis, experiments, and bibliometric analysis (Ali & Naveed, 2020;Allam, 2020;Caliskan, Akin, & Engin-Demir, 2020;Du, Yang, Shelton, Hung, & Zhang, 2021;Gomez, 2020;Hayes & Findlow, 2020;Kuzhabekova, 2021;Shoaib & Ullah, 2021b;Tripathi, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most of these studies concluded that the academic performance of students had not based on a single factor (Loo, 2017;Lynch & Hennessy, 2017;Mollaeva, 2017;Nogueira, Barros, & Sequeira, 2017;Shoaib, Tariq, Shahzadi, & Ali, 2022). Multiple factors were contributing including classroom environment (Blewitt & Shane, 2019;Shoaib, Anwar, & Rasool, 2022), students' home background (Boateng, Asare, Manu, Sefah, & Adomako, 2020;, study culture (Houtte, 2004;Shoaib, Ali, Anwar, & Abdullah, 2022), the role of teacher Dee, 2006), previous education (Ali et al, 2022;Selvig, Holaday, Purkiss, & Hortsch, 2015), and personal efforts (Arshad, Zaidi, & Mahmood, 2015;Shoaib & Ullah, 2021a). On the other hand, several researchers used different methodological approaches to study students' academic performance in higher education institutions including qualitative, quantitative, mixed methods, observation, content analysis, experiments, and bibliometric analysis (Ali & Naveed, 2020;Allam, 2020;Caliskan, Akin, & Engin-Demir, 2020;Du, Yang, Shelton, Hung, & Zhang, 2021;Gomez, 2020;Hayes & Findlow, 2020;Kuzhabekova, 2021;Shoaib & Ullah, 2021b;Tripathi, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%